Influence of Job Stress and Safety Climate on Safety Performance in Indonesia Rock Mining Company - Muhammad Rifqi (Universitas Airlangga, 2022)
This study was carried out in one of Indonesia's rock mining companies. This company conducts mining operations with heavy equipment and strict safety protocols to ensure that mining is carried out safely. However, there are still a lot of accidents and complaints at this firm, and the employees are stressed out. This research aims to understand more about the safety climate and job stress and how they affect safety performance. An organization's perception of safety hazards in their workplace is known as the safety climate. Job stress is defined as a feeling of strain caused by an excessive workload and mental and emotional tension, which might impede individual performance. The quality of employee performance about safety objectives is referred to as safety performance. This study was carried out on all 85 employees of a mining company in Jambi, Indonesia, in the stone mining division. Using SPSS, this study used multiple linear regression to determine the impact of two factors on safety performance: safety climate and job stress. A simple linear regression test was used to examine the effect of safety performance on reputation and productivity. A simple linear regression test was used to investigate the impact of safety performance on reputation and productivity. A simple linear regression test was used to examine the effect of safety performance on reputation and productivity. The findings revealed that the two factors impacted safety performance if the sig value was less than 0.05 in this investigation. This study also discovered that performance level reputation and productivity.